J-point elevation in survivors of primary ventricular fibrillation and matched control subjects: incidence and clinical significance - Rosso, Raphael; Kogan, Evgeni; Belhassen, Bernard; Rozovski, Uri; Scheinman, Melvin M; Zeltser, David; Halkin, Amir; Steinvil, Arie; Heller, Karin; Glikson, Michael; Katz, Amos; Viskin, Sami (Journal of the American College of Cardiology, 2008)
The purpose of this study was to determine whether J-point elevation is a marker of arrhythmic risk. J-point elevation has been considered an innocent finding among healthy young individuals (the "early repolarization" pattern). However, this electrocardiogram (ECG) finding is increasingly being associated with idiopathic ventricular fibrillation (VF). In a case-control study, the ECG of 45 patients with idiopathic VF were compared with those of 124 age- and gender-matched control subjects and with those of 121 young athletes. We measured the height of J-point and ST-segment elevation and counted the presence of slurring in the terminal portion of the R-wave. J-point elevation was more common among patients with idiopathic VF than among matched control subjects (42% vs. 13%, p = 0.001). This was true for J-point elevation in the inferior leads (27% vs. 8%, p = 0.006) and for J-point elevation in leads I to aVL (13% vs. 1%, p = 0.009). J-point elevation in V(4) to V(6) occurred with equal frequency among patients and matched control subjects (6.7% vs. 7.3%, p = 0.86). Male subjects had J-point elevation more often than female subjects and young athletes had J-point elevation more often than healthy adults but less often than patients with idiopathic VF. The presence of ST-segment elevation or QRS slurring did not add diagnostic value to the presence of J-point elevation. J-point elevation is found more frequently among patients with idiopathic VF than among healthy control subjects. The frequency of J-point elevation among young athletes is intermediate (higher than among healthy adults but lower than among patients with idiopathic VF).